The effect of type of paragraph on native and non-native English speakers' use of grammatical cohesive devices in writing and raters' evaluation - Saadat, Mahboobeh; Alavi, Sahar Zahed (Penerbit Universiti Kebangsaan Malaysia, 2018)
The present study examined the use of grammatical cohesive features in two types of paragraphs (chronologyvs. cause-effect) written by EFL learners and native speakers. In addition, the study investigated if the use of grammatical cohesive devices affected raters' evaluation of the paragraphs written by the EFL learners. To investigate the non-native speakers’ performances, 60 paragraphs) 30 cause-effect and 30 chronology paragraphs) written by 30 intermediate Iranian EFL learners were examined. Furthermore, to investigate those of native speakers, 20 paragraphs (10 cause-effect and 10 chronology paragraphs) were randomly selected from among the sample paragraphs presented in books teaching paragraph writing written by English native speakers. To analyze the data, Halliday and Hasan's (1976) taxonomy of cohesive devices was used, and MANOVA was conducted. To investigate raters’ judgments, four raters were asked to rate the paragraphs written by six randomly selected learners. The results showed that EFL learners more frequently used reference, conjunction, ellipsis and substitution, respectively in their chronology and cause-effect paragraphs. However, in their paragraphs of chronology, native speakers more frequently used reference, conjunction, ellipsis and substitution, respectively whereas in their paragraphs of cause-effect, they frequently used reference, conjunction, substitution, and ellipsis, respectively. A comparison of the performance of native speakers and non-native speakers revealed that native speakers used more reference in their paragraphs than non-natives did. As for raters’ judgments, the findings indicated that cohesion in the paragraphs was generally ignored by some raters.